2006
DOI: 10.1577/t04-078.1
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Morphology among Juvenile Chinook Salmon of Hatchery, Hybrid, and Wild Origin

Abstract: Body morphology differed significantly between juvenile hatchery Chinook salmon Oncorhynchus tshawytscha that have experienced five generations of hatchery culture and juveniles derived from the wild founding stock and cultured in the same environment. All lines tested were raised in a similar hatchery environment. Thin‐plate spline analysis was used to characterize the morphometric variation among these lines of fish. Hatchery fish had a more compressed body, a narrower head, shorter maxillae, and a longer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Both the genetic and environmental components can be involved in morphological differences between hatchery and wild stocks (Swain et al 1991;Wessel et al 2006), and the degree of divergence from the wild state is determined by both the proportion of an individual's life spent in hatchery and the number of hatchery generations . Nevertheless, a homogenous environment may generate partly reversed, convergent effects because of strong adaptive responses of salmonid to altered selection pressures ).…”
Section: Discussionmentioning
confidence: 99%
“…Both the genetic and environmental components can be involved in morphological differences between hatchery and wild stocks (Swain et al 1991;Wessel et al 2006), and the degree of divergence from the wild state is determined by both the proportion of an individual's life spent in hatchery and the number of hatchery generations . Nevertheless, a homogenous environment may generate partly reversed, convergent effects because of strong adaptive responses of salmonid to altered selection pressures ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the smaller fins of the cultured cod resulted in part from a plastic response to water current. Studies in salmonids have shown that lower current velocity and variability experienced in culture can lead to relatively smaller fins (Pakkasmaa & Piironen 2000, Wessel et al 2006, Keeley et al 2007. Similarly, when compared to wild fish, farmed cod likely experience similar reductions in water velocity, and hence similar plastic effects on fin size could be expected in our study.…”
Section: Differences Between Wild and Farmed Fishmentioning
confidence: 99%
“…Two basic patterns have been seen in hatchery fish, depending on the type of hatchery environment. ''Farmed'' fish (fish that are reared to adulthood in captivity) tend to be deeper bodied than wild fish (Webb et al 1991;Hard et al 2000), but ''sea-ranched'' fish (hatchery fish that are released as juveniles into the natural environment) tend to display the more streamlined phenotype typical of fish better adapted for sustained swimming (Taylor 1986;Fleming and Gross 1989;Swain et al 1991;Wessel et al 2006). Hatchery fish, both farmed and sea ranched, also show reduced snout development and important secondary sexual characteristics (Fleming and Gross 1989;Petersson and Jarvi 1993;Hard et al 2000).…”
mentioning
confidence: 99%
“…More studies of morphological change, as well as domestication in general, need to be done on fish with the same genetic background. The morphological studies of and Wessel et al (2006) have done this, but in populations with substantial cultural histories. No study to date has addressed the development of morphological change as domestication proceeds in a previously wild population.…”
mentioning
confidence: 99%